European Retail Research 2008 / Volume 22 - Swoboda, Bernhard; Morschett, Dirk; Rudolph, Thomas; Schnedlitz, Peter; Schramm-Klein, Hanna (European Retail Research,, 2009)
The aim of EUROPEAN RETAIL RESEARCH is to publish interesting manuscripts of high quality and innovativeness with a focus on retail researchers, retail lecturers, retail students and retail executives. As it has always been, retail executives are part of the target group and the knowledge transfer between retail research and retail management remains a part of the publication's concept. EUROPEAN RETAIL RESEARCH welcomes manuscripts on original theoretical or conceptual contributions as well as empirical research - based either on large-scale empirical data or on the case-study method. Following the state of the art in retail research, articles on any major issues that concern the general field of retailing and distribution are welcome. The review process will support the authors in enhancing the quality of their work and will offer the authors a reviewed publication outlet. Part of the concept of EUROPEAN RETAIL RESEARCH is an only short delay between manuscript submission and final publication, so it is intended to become a quick publication platform.